2005
DOI: 10.1128/jcm.43.2.556-564.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Environmental and Clinical Populations ofCryptococcus neoformans

Abstract: Cryptococcus neoformans is a major, global cause of meningoencephalitis in immunocompromised patients. Despite advances in the molecular epidemiology of C. neoformans, its population structure and mode of reproduction are not well understood. In the environment, it is associated with avian guano or vegetation. We collected nearly 800 environmental isolates from three locations in the United States (viz., North Carolina, California, and Texas) and compared them with one another and with clinical isolates from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
147
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 43 publications
11
147
4
1
Order By: Relevance
“…The remaining 92 were MATa and were from different parts of the world, including Botswana. As expected, the Botswana population that contained strains of both mating types showed evidence of recombination and sexual reproduction (Litvintseva et al, 2003(Litvintseva et al, , 2006. In contrast, the remaining geographical populations that contained only MATa strains were largely clonal, with no clear evidence of recombination.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The remaining 92 were MATa and were from different parts of the world, including Botswana. As expected, the Botswana population that contained strains of both mating types showed evidence of recombination and sexual reproduction (Litvintseva et al, 2003(Litvintseva et al, , 2006. In contrast, the remaining geographical populations that contained only MATa strains were largely clonal, with no clear evidence of recombination.…”
Section: Introductionmentioning
confidence: 74%
“…For example, an MLST study of the population structure of C. neoformans var. grubii involving 102 representative strains from different parts of the world showed that the global population contained three genetically distinct subgroups (Litvintseva et al, 2006). Ten of the 102 strains were MATa and they were all from Botswana.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results obtained have been variable, most authors have suggested that persistence or recurrence of the infection might be caused by relapse rather than reinfection and/or micro-evolution of the original isolate (Jain et al, 2005;Litvintseva et al, 2005). A multi-strain infection was rarely considered until a recent Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a long-recognized laboratory a-a sexual cycle, an overwhelming number of environmental and clinical isolates are of just one mating type, MATa (Kwon-Chung and Bennett 1978; Halliday et al 1999). In many pathogenic fungi, including C. neoformans, the population is largely clonal, yet these organisms maintain their ability to undergo both bisexual and unisexual reproduction (Litvintseva et al 2003(Litvintseva et al , 2005. In particular, clinical isolates of C. neoformans often are derived from large clonal populations of environmental isolates that show evidence of recombination, despite the paucity of MATa isolates in some sampled populations.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive sampling of C. neoformans populations revealed .99% of cells are MATa (Lengeler et al 2000;Litvintseva et al 2003Litvintseva et al , 2005Heitman 2010). The preponderance of MATa cells raises the question of how frequently C. neoformans undergoes sexual reproduction in natural populations.…”
mentioning
confidence: 99%